Polar vortex hidden in twisted bilayers of paraelectric SrTiO3 - Haozhi Sha; Yixuan Zhang; Yunpeng Ma; Wei Li; Wenfeng Yang; Jizhe Cui; Qian Li; Houbing Huang; Rong Yu (Nature Communications)
Abstract Polar topologies, such as vortex and skyrmion, have attracted significant interest due to their unique physical properties and promising applications in high-density memory devices. To date, all known polar vortices are present in or induced by ferroelectric materials. In this study, we find polar vortex arrays in paraelectric SrTiO3. Using multislice electron ptychography, the evolution of vorticity along the vortex axis is revealed in twisted bilayers of SrTiO3 with deep-sub-angstrom resolution and one picometer accuracy. The surprising finding of polar vortices in a paraelectric crystal opens up opportunities for polarization physics and corresponding new devices.